2013
DOI: 10.1016/j.cmet.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

LXRs Regulate ER Stress and Inflammation through Dynamic Modulation of Membrane Phospholipid Composition

Abstract: The fatty acyl composition of phospholipids determines the biophysical character of membranes and impacts the function of membrane proteins. Here we define a nuclear receptor pathway for the dynamic modulation of membrane composition in response to changes in cellular lipid metabolism. Ligand activation of LXR preferentially drives the incorporation of polyunsaturated fatty acids into phospholipids through induction of the remodeling enzyme Lpcat3. Promotion of Lpcat3 activity ameliorates ER stress induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
306
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 266 publications
(339 citation statements)
references
References 36 publications
16
306
2
1
Order By: Relevance
“…Acute knockdown of liver Lpcat3 in genetically obese mice exacerbates lipid-induced ER stress (8). However, the same group recently reported that Lpcat3 deficiency in the liver does not affect the expression of ER stress markers (9).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Acute knockdown of liver Lpcat3 in genetically obese mice exacerbates lipid-induced ER stress (8). However, the same group recently reported that Lpcat3 deficiency in the liver does not affect the expression of ER stress markers (9).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that Lpcat3 protects against ER stress in the liver (8). To determine whether this also applies to the small …”
Section: Lpcat3 Deficiency Significantly Decreases Lipid Absorption Imentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent study, LXR signaling is indeed involved in the dynamic modulation of membrane lipid composition by promoting the incorporation of unsaturated fatty acids into phospholipids in response to changes in cellular lipid metabolism. This LXR-mediated phospholipid remodeling might affect the biophysical characteristics of biological membranes and thus might also be involved in the modification of transmembrane protein function (Rong et al, 2013). …”
Section: Au6mentioning
confidence: 99%